Allah speaks to the prophet musa ; Quran stories for little hearts - Khan , Saniyasnain (India : Goodwordsbook, 2011)
Allah Speaks to the Musa" is a thought-provoking exploration of spirituality, faith, and the relationship between God and humanity. The book presents a fictional dialogue between Allah and Musa (Moses), delving into themes of divine guidance, the struggles of faith, and the quest for understanding one's purpose. Through this interaction, readers are invited to reflect on their beliefs, the nature of God, and the challenges faced in living a life aligned with spiritual values. The narrative emphasizes compassion, wisdom, and the importance of seeking truth. Overall, it serves as a contemplative journey that encourages readers to deepen their connection with the divine.
Keywords: English - Text book